Mathematical exploration ability and students’ habits of mind based on gender: a study in junior high school level - Veven, Veven; Bistari, Bistari; Fitriawan, Dona; Hamdani, Hamdani; Rustam, Rustam; Dashela, Tarina (Institute of Advanced Engineering and Science, 2024)
In learning mathematics, students tend to only be directed to get good results, without paying attention to how the exploration process of the problems given. In fact, the exploration process that students go through is different from one another and influenced by certain factors. The objective of this study is to describe the mathematical exploration ability on number pattern topic studied from the students’ habits of mind based on gender at the junior high school level. This study used mixed methods with sequential-explanatory model, and involved 27 students of grade VIII (second year). The instruments used include a test of mathematical exploration ability, habits of mind questionnaire, and an interview guidelines. The results revealed that there are differences in mathematical exploration ability between male and female students where some of the differences are caused by their habits of mind. Female students tended to be more able to explore mathematical problems than male students, because they applied more habits of mind than male students when trying to solve the problem. This also shows that habits of mind affect students’ mathematical exploration ability.